Social Media and Citizens` Participations in Politics in a Multi-Cultural Society like Nigeria - Jammy Seigha Guanah (Polit Journal Scientific Journal of Politics, 2025)
Social media have become important tools for political participation worldwide, and Nigeria is not an exception. With a multi-cultural society like Nigeria, social media provide platforms for citizens to engage in politics, discuss issues, and participate in the political process. The objectives of this research paper were to determine if respondents engage in politics through social media; ascertain the social media platforms through which respondents participate in politics, and determine the nature of their participation through social media. The study was hinged on the Agenda-Setting Theory. It was conducted through a survey of 500 participants selected from Midwestern Nigeria (Delta and Edo States). The findings revealed that social media play a significant role in citizens' participation in politics in Nigeria, and that respondents use various social media platforms to engage in politics. The study also revealed that citizens' participation through social media is mostly limited to discussions, sharing of information, and social advocacy. This study concluded that social media play significant roles in citizens' participation in politics in a multicultural society like Nigeria. It was therefore recommended that there should be the development of online civic education initiatives that provide citizens with comprehensive knowledge about political processes, institutions, and their rights and responsibilities. Also, there is the need for increased education and awareness on the use of social media for political participation. Further, itizens need to be educated on how to use social media platforms for political activities and how to differentiate between credible and fake news.